Influência dos mecanismos fisiopatológicos da hiperprolactinemia moderada na ovulação de mulheres inférteis - Sanchez, Eliane Gouveia de Morais (2015)
Infertility reflects the inability of a couple to achieve pregnancy after one year of sexual intercourse without contraception. Most common causes are related to ovulatory disorders such as hyperprolactinaemia, polycystic ovary syndrome, thyroid dysfunction, corpus luteum deficiency, among others, and can be identified mainly by ultrasound and hormonal dosage. The overall objective of this study was to evaluate the influence of prolactin ovulation in infertile women suffering from regular cycles. It is case-control study, whose sample consisted of 343 women with age range 20-40 years old, attended from 2000 to 2014 in LabRep-HC / UFG and an office of Obstetrics and Gynecology, private network in Goiânia, Goiás, Brazil. Data collection was performed by analyzing the physical records stored in Medical Records and Health Information Service (SAMIS) and electronics made available by the database (Sisfert) (© Approbato, 2013). The patients were classified according to the ovulation state measured by progestogen dosage (≥ 5.65 ng / ml and 5.65 - 9.9 ng / ml) and ovulation by monitoring the ultrasound being divided into four groups: (I ) probable ovulation, (II) likely anovulation. In Groups I and II were compared with the percentages of patients who do not ovulate with normal prolactin (3 to 20 ng / ml) versus moderately elevated prolactin (21 to 29 ng / ml). In group III were evaluated Normal progesterone levels (≥ 10 ng / mL) versus low progesterone (Group IV) (5.65 - 9.9 ng / ml) was considered as LUF (non-luteinized ruptured follicle). The groups were comparable for comparable as to age, body mass index (BMI), duration of infertility, FSH (ng / ml) TSH (mIU / l), LH (IU / l) and oestradiol (ng / dL) . SPSS Statistics 20.0 software and Bioestat (version 5.3) were used to for data analysis and chi-square test (X2) to assess differences between proportions. Where it is not for statistical analysis were calculated mean and standard deviation of the variables under study. The results demonstrated that moderate elevation of prolactin (21-29 ng / ml) caused a significant reduction (p = 0.03) in the ovulation rate of infertile patients with regular cycles considering as a criterion for ovulation progesterone levels ≥5, 65 ng / ml. When evaluated the influence of low progesterone on ovulation monitored by ultrasound was observed that these levels can significantly reduce the percentage of ovulation. It is concluded that a moderate hyperprolactinaemia and low progesterone can negatively influence the regulation of ovulation in infertile women with regular menstrual cycles.